HUMAN RESOURCES MANAGEMENT STRATEGY BASED ON COMPETENCE PARTY NASIONAL DEMOKRAT PERIOD 2019 - 2024 - Agus Istomo; Indra Budi Sumantoro; Rinderiyana Rinderiyana (Proceeding International Conference on Information Technology and Business, 2019)
KPU of Bandar Lampung City has carried out the Open Plenary Meeting Determination of the Obtained Seat of Political Parties and Elected Candidates of Bandar Lampung City DPRD Election in 2019, Monday (12/8), Nasdem ranked sixth by sending five representatives to the DPRD of Bandar Lampung City. Paying close attention to the composition of the management that has now been carried out a deeper search of the management of DPD NasDem Bandar Lampung City which includes background, education, competence (knowledge, skills, experience) to find data / facts not in accordance with the actual / reality. The research method used was qualitative Gap analysis. The results of research conducted according to the spancer spancer dictionary obtained the highest gap is ORGANIZING AWARENESS (ORGANITATIONAL AWARENESS, OA) Dimension B. Power of organizational understanding, while the lowest gap is THE SPIRIT TO ACHIEVE or TO ACHIEVE THE WORK TARGET (ACHIEVEMENT ORIENTATION, ACH) the next of the lowest Gap will be held trainings to improve competence in particular to excel and to do employment targetsKeywords: Strategy, HRM, Competence